Pseudomonas-Enterobacter Co-Infection Drives Cellulitis and Lymphangitis in Equines: A Case Report - Xiangning Huang; Renjie Deng; Haoen Huang; Huisheng Xie; Aolei Chen (Veterinary Sciences, 2025)
This case report detailed a rare co-infection of Pseudomonas asiatica and Enterobacter hormaechei in a 9-year-old warmblood mare, leading to severe cellulitis and secondary lymphangitis following traditional hoof blood-letting therapy. The mare exhibited acute limb swelling, fever, cutaneous ulceration, lymphatic dysfunction and unknown anemia. Comprehensive diagnostics, including bacterial culture, whole-genome sequencing, anti-elastin antibody (AEAb) ELISA, and diagnostic imaging, confirmed the pathogens causing cellulitis and secondary lymphangitis. AEAb levels were elevated, correlating with lymphatic degradation, while radiography and lymphangiography ruled out laminitis but identified tortuous lymphatic vessels. The treatment integrated systemic antimicrobials, anti-inflammatory therapy, combined decongestive therapy, and traditional Chinese herbal medicine, resulting in resolution of infection, improved hematological parameters, and restored athletic performance. The therapeutic regimen primarily included gentamicin, enrofloxacin, oxytetracycline, and the Wei Qi Booster. The case highlights the critical role of pathogen-directed antimicrobial selection and the potential benefits of combining conventional and holistic therapies. This report emphasizes the necessity of early, multifaceted interventions to prevent life-threatening complications in equine cellulitis–lymphangitis cases.